Aural toilet (ear cleaning) for chronic suppurative otitis media - Bhutta, Mahmood F; Head, Karen; Chong, Lee Yee; Daw, Jessica; Schilder, Anne Gm; Brennan-Jones, Christopher G (Cochrane database of systematic reviews, 2025)
Chronic suppurative otitis media (CSOM), sometimes referred to as chronic otitis media, is a chronic inflammation and often polymicrobial infection of the middle ear and mastoid cavity, characterised by ear discharge (otorrhoea) through a perforated tympanic membrane. The predominant symptoms of CSOM are ear discharge and hearing loss. Aural toileting describes processes for manually cleaning the ear, including dry mopping (with cotton wool or tissue paper), suction clearance (typically under a microscope), or irrigation (using manual or automated syringing). Aural toileting can be used alone or in addition to other treatments for CSOM, such as antibiotics or topical antiseptics. This is one of a suite of seven Cochrane reviews evaluating the effects of non-surgical interventions for CSOM. This is the first update of a Cochrane review published in 2020. To assess the benefits and harms of aural toilet procedures for people with chronic suppurative otitis media. We searched the Cochrane ENT Register, CENTRAL, Ovid MEDLINE, Ovid Embase, and five other databases. We also searched ClinicalTrials.gov and the World Health Organization International Clinical Trials Registry Platform (ICTRP). The searches were run on 15 June 2022. We included randomised controlled trials with at least a one-week follow-up involving adults or children who had chronic ear discharge of unknown cause or CSOM, where the ear discharge had continued for more than two weeks. We included any aural toileting method as the intervention, at any frequency, and for any duration. The main comparisons were aural toileting versus placebo or no intervention, and one aural toileting method versus another aural toileting method. Within each comparison, we separated studies into those in which both groups received other concomitant treatments (e.g. antiseptics or antibiotics) and those without concomitant treatments. We used standard Cochrane methodology. Our primary outcomes were resolution of ear discharge or 'dry ear' (whether otoscopically confirmed or not), measured at one week to up to two weeks, two weeks to up to four weeks, and after four weeks; health-related quality of life using a validated instrument; and ear pain (otalgia) or discomfort or local irritation. Secondary outcomes were hearing, serious complications, and adverse events (dizziness/vertigo/balance problems, ear bleeding). We used GRADE to assess the certainty of the evidence for each outcome. This update did not find any new studies. We included three studies with 431 participants (465 ears) reporting on two comparisons. Two studies included only children with CSOM in the community (351 participants) and the other study (80 participants) included children and adults with chronic ear discharge for at least six weeks. One study recruited participants from the Solomon Islands, who were considered a 'high-risk' Indigenous group. None of the included studies reported health-related quality of life, ear pain, or ear bleeding. 1. Daily aural toileting versus no treatment Two studies (351 children; 370 ears) compared daily dry mopping with no treatment. For resolution of ear discharge after four weeks, only one study reported the results per person. We are very uncertain whether there is a difference at 16 weeks (risk ratio (RR) 1.01, 95% confidence interval (CI) 0.60 to 1.72; 1 study, 217 participants; very low-certainty evidence). There were no results reported for the adverse events of dizziness, vertigo, or balance problems. Only one study reported serious complications, but it was not clear which group these participants were from, or whether the complications occurred pre- or post-treatment, and therefore the certainty of evidence was very low. One study reported hearing, but the results were presented by treatment outcome rather than by treatment group, so it was not possible to determine whether there was a difference between the two groups. 2. Daily aural toileting versus single aural toileting episode (both in addition to topical ciprofloxacin) One study (80 participants; 95 ears) compared daily aural toileting (suction) with administration of topical antibiotic (ciprofloxacin) ear drops in a clinic, to a single aural toileting (suction) episode followed by daily self-administered topical antibiotic drops, in participants of all ages. We are very uncertain if there is a difference in resolution of ear discharge at between one and up to two weeks (RR 1.09, 95% CI 0.91 to 1.30; 1 study, 80 participants; very low-certainty evidence). The results for resolution of ear discharge after four weeks were presented by ear, not person, and could not be adjusted to by person. The authors only reported qualitatively that there was no difference between the two groups in hearing results (very low-certainty evidence). One participant in the group with single aural toileting and self-administration of topical antibiotic ear drops reported the adverse event of dizziness, which the authors attributed to the use of cold topical ciprofloxacin. It is very uncertain whether there is a difference between the groups (RR 0.33, 95% CI 0.01 to 7.95; 1 study, 80 participants; very low-certainty evidence). There were no results reported for the other adverse events of vertigo or balance problems, or for serious complications. We are very uncertain whether treatment with aural toileting is effective in resolving ear discharge in people with CSOM when compared to no treatment, due to a lack of data and the poor quality of the available evidence. The evidence was considered very low-certainty as there were concerns over risk of bias, indirectness, imprecision, and suspected publication bias. We also remain uncertain about other outcomes, including adverse events, as these were not well reported. Similarly, we are very uncertain whether daily suction clearance, followed by antibiotic ear drops administered at a clinic, is better than a single episode of suction clearance followed by self-administration of topical antibiotic ear drops. Limitations of the review include lack of recency in data, and limited information on certain population groups or interventions.